2020
DOI: 10.1038/s41598-020-75603-7
|View full text |Cite
|
Sign up to set email alerts
|

Long sequence single-exposure videography using spatially modulated illumination

Abstract: Frequency recognition algorithm for multiple exposures (FRAME) is a single-exposure imaging technique that can be used for ultrafast videography, achieved through rapid illumination with spatially modulated laser pulses. To date, both the limit in sequence length as well as the relation between sequence length and image quality are unknown for FRAME imaging. Investigating these questions requires a flexible optical arrangement that has the capability of reaching significantly longer image sequences than curren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…A drawback with the FRAME technique is that the number of frames in the sequence is limited. However, it has previously been demonstrated that hundreds of signals can be multiplexed in this way 39 , and our results (Fig. 4 b) suggest that it could be sufficient with a Fourier space area as small as pixels ( corresponds to a filter radius of 50 pixels) to capture all relevant signal, while still avoiding cross-talk between signals.…”
Section: Discussionmentioning
confidence: 56%
See 3 more Smart Citations
“…A drawback with the FRAME technique is that the number of frames in the sequence is limited. However, it has previously been demonstrated that hundreds of signals can be multiplexed in this way 39 , and our results (Fig. 4 b) suggest that it could be sufficient with a Fourier space area as small as pixels ( corresponds to a filter radius of 50 pixels) to capture all relevant signal, while still avoiding cross-talk between signals.…”
Section: Discussionmentioning
confidence: 56%
“…This amplitude is either reduced by the sample through e.g. light extinction 38 , 39 or is increased due to e.g. fluorescence 43 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In FRAME, the spatial modulation is usually achieved by introducing a transmission Ronchi grating in the path of the conventional laser beam of homogenous intensity. The other means to spatially modulate the laser beam can be a digital micromirror device (DMD) [37] or a two-faceted optical component [38]. In FRAME, judiciously, each "coded" illumination probing a different species is sent from different angles towards the incident plane (usually cross-patterned for two species) for probing the sample (see Fig.…”
Section: Introductionmentioning
confidence: 99%